P66Shc-Induced MicroRNA-34a Causes Diabetic Endothelial Dysfunction by Downregulating Sirtuin1. Issue 12 (December 2016) - Li, Qiuxia; Kim, Young-Rae; Vikram, Ajit; Kumar, Santosh; Kassan, Modar; Gabani, Mohanad; Lee, Sang Ki; Jacobs, Julia S.; Irani, Kaikobad
Abstract : Objective—: Diabetes mellitus causes vascular endothelial dysfunction and alters vascular microRNA expression. We investigated whether endothelial microRNA-34a (miR-34a) leads to diabetic vascular dysfunction by targeting endothelial sirtuin1 (Sirt1) and asked whether the oxidative stress protein p66Shc governs miR-34a expression in the diabetic endothelium. Approach and Results—: MiR-34a is upregulated, and Sirt1 downregulated, in aortic endothelium of db/db and streptozotocin-induced diabetic mice. Systemic administration of miR-34a inhibitor, or endothelium-specific knockout of miR-34a, prevents downregulation of aortic Sirt1 and rescues impaired endothelium-dependent aortic vasorelaxation induced by diabetes mellitus. Moreover, overexpression of Sirt1 mitigates impaired endothelium-dependent vasorelaxation caused by miR-34a mimic ex vivo. Systemic infusion of miR-34a inhibitor or genetic ablation of endothelial miR-34a prevents downregulation of endothelial Sirt1 by high glucose. MiR-34a is upregulated, Sirt1 is downregulated, and oxidative stress (hydrogen peroxide) is induced in endothelial cells incubated with high glucose or the free fatty acid palmitate in vitro. Increase of hydrogen peroxide and induction of endothelial miR-34a by high glucose or palmitate in vitro is suppressed by knockdown of p66shc. In addition, overexpression of wild-type but not redox-deficient p66Shc upregulates miR-34a in endothelial cells. P66Shc-stimulated upregulation of endothelial miR-34a is suppressed by cell-permeable antioxidants. Finally, mice with global knockdown of p66Shc are protected from diabetes mellitus–induced upregulation of miR-34a and downregulation of Sirt1 in the endothelium. Conclusions—: These data show that hyperglycemia and elevated free fatty acids in the diabetic milieu recruit p66Shc to upregulate endothelial miR-34a via an oxidant-sensitive mechanism, which leads to endothelial dysfunction by targeting Sirt1. Abstract : Supplemental Digital Content is available in the text.